Estilos lingüísticos y el desarrollo del lenguaje en la primera infancia. - Sasig Pilatasig, Jhoselyn Lisbeth (2022)
The purpose of this research project is to analyze linguistic styles and language development in early childhood at the "Ramón Barba Naranjo" Educational Unit. The objective of this work is aimed at making a diagnosis to determine linguistic styles and language development in early childhood. In this way it was possible to show certain cases with shortcomings in the development of language and the use of linguistic styles. This research has a mixed qualitative and quantitative approach, the research is exploratory, descriptive in such a way that the project turned out to be viable and applied; the techniques used are: the survey of parents, checklist and observation technique applied to children in the classroom of Initial II "A". According to the global results obtained, 68% correctly reach the use of linguistic styles and their language development in the classroom, in the same way it was determined that 25% are in the process of developing it, for which suggests the use of new strategies in the classroom and in this way correctly develop the language and its different styles; Finally, a low index that is 7% is in the beginning process, in such a way that the implementation of strategies for language and help from home is suggested. Concluding with the investigation, the development of language and its linguistic styles in early childhood is of great importance in the educational and social part since it is a means of communication towards the environment in which it is found; Through the application and interpretation of data, a very low rate of children who present some difficulty at the time of communication is visualized.